Disconnect between sympathetically-induced hunger suppression and consumption among highly restrained eaters following stress. (1st February 2023) - McGeown, Laura; De Young, Kyle P.; Mushquash, Aislin R.
Abstract: Despite emphasis on findings suggesting restrained eaters increase food consumption under stress, unrestrained eaters' reduction in intake is more robust. Early proposals asserted unrestrained eaters significantly reduced intake after certain threats due to the hunger-inhibiting effects of autonomic influences, presuming unrestrained eaters are more responsive to these effects and restrained eaters rely less on physiological cues for eating. However, scant empirical evidence has substantiated these claims. This study examined whether a sequence exists whereby stress elicits autonomic activation, autonomic activation impacts hunger, and hunger then impacts eating, with dietary restraint altering the hunger-intake link. It was hypothesized that sympathetic nervous system activation would be greatest when ongoing safety from stress was uncertain, sympathetic activation would be linked to reduced hunger, and lower hunger would be associated with attenuated intake. Restraint, conceptualized via Hagan et al.'s (2017) latent restraint factors, was hypothesized to reduce the association between hunger and intake. Female participants ( n  = 147) were randomized to a stress + certain safety, stress + uncertain safety, or control condition. Sympathetic nervous system activity was recorded prior to a bogus taste test, which quantified ad libitum consumption of highly-palatable snack foods post-stress. Only the stress + uncertain safety condition exhibited greater sympathetic nervous system activity than the control condition. A significant index of moderated serial mediation emerged for Preoccupation with Dieting and Weight-Focused Restraint in the stress + uncertain safety condition. Though sympathetic activation decreased hunger similarly regardless of dietary restraint, only less restrained individuals significantly decreased intake. More restrained individuals ate more despite experiencing lower hunger. The disconnect between hunger and intake in more restrained eaters suggests that focus on enhancing attunement to hunger may yield greater benefit than enhancing restraint. 281 words .